Primary carcinoma of the fallopian tube - Esteves Flores, Luis (2015)
The authors have studied 9 cases of primary carcinoma of the Fallopian tube; this means an incidence of 0.09 % in a total of 9266 malignant tumors of the genital tract observed at the Instituto Nacional de Enfermedades Neoplásicas, Lima Perú, between 1952 and 1966. The patients had an average age of 50 years, range 33-70; the treatment was surgical and radiation, and the overall survival rate was 22 %.